RESPON PEMBERIAN PUPUK HAYATI BIONEENSIS TERHADAP PERTUMBUHAN JUMLAH MATA TUNAS TANAMAN JAHE MERAH - Delia Eka Novita; Siti Khairani; Juhardi Sembiring (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2023)
Ginger is an agricultural commodity that has good opportunities and prospects for development. Bioneensis biofertilizer contains bacteria isolated from oil palm roots and has many benefits for plants. This study aims to determine the effect of biofertilizer application bioneensis on the growth of the number of shoots and the production of red ginger (zingiber officinale var. Rubrum). This study used a factorial randomized blok design with 2 factors and 3 replications. Giving bioneensis (B) consists of 4 levels, namely B0 (0 gr/polybag), B1 (20gr/polybag), B2 (40 gr/polybag), and B3 (60 gr/polybag). The number of buds consists of 4 levels, namely M1(1 mata tunas), M2 (2 mata tunas), M3 (3 mata tunas), and M4 (4 mata tunas). The results of the study gave a very significant effect on the parameters, namely plant height (cm) and the effect was not significant on parameters, number of leaves (helai), number of tillers per polybag, and canopy dry weight (gr). While the results of the study on the application of biofertilizer bioneensis and the number of buds showed no significant effect on all parameters, namely plant height (cm), number of leaves (helai), number of tillers per polybag, and canopy dry weight (gr). The best treatment was found in the parameters of plant height with a dose of 60% bioneensis and the number of shoots 2 with an average yield of 77.17 cm.